AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ALOKASI DANA DESA (Studi kasus di Desa Kebonbatur, Kec. Mranggen, Kab.Demak) - Rahmadini, Giovani Putri; Amalia, Naini Rizka (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This research was conducted to determine the Accountability and Transparency of Village Fund Allocation Management in Kebonbatur Village, Mranggen District, Demak Regency in the context of management accountability starting from the planning, implementation, accountability and supervision stages in Kebonbatur Village, Mranggen District, Demak Regency, in accordance with the Regulation of the Minister of Home Affairs No. 20 of 2018 concerning Village Financial Management. This research uses a qualitative method of descriptive analysis, with data collection using in-depth interview techniques, direct observation and documentation. To test the validity of the data using triangulation of data sources and triangulation of data collection techniques. The research data sources in in-depth interviews are participants who have a position or authority in the object of research, namely as many as 3 (three) participants based on the principles of suitability and adequacy. The results of this study indicate that accountability and transparency in the management of village fund allocations in Kebonbatur Village are very accountable and transparent in managing village fund allocations starting from the planning, implementation, accountability and supervision stages. Keywords: Accountability, Transparency, Village Fund Allocation